Optimizing position, promotion and distribution strategies to encourage the discovery and adoption of alternative proteins on the French market - Rougeron, Grégory Sylvain Claude (2024)
The significant growth in alternative proteins (AP) has stimulated the adoption of plant-based meat. Reducing environmental impact, boosting animal welfare, preserving biodiversity, and health concerns are all reasons to adopt such products. More and more people worldwide are becoming ‘flexitarian’ and aiming to reduce their consumption of animal proteins. AP producers such as HappyVore, Impossible Foods and Ynsect are responding to this growing demand. At the same time, retailers adapt their assortments and choice of suppliers to cater for this promising segment. While this is a global phenomenon, the adoption of APs is slow in France, where consumers may be reluctant to take this step. Given current regulations, only plant-based proteins are sold on this market, whereas other countries have already taken the step towards lab-cultivated meat (Singapore, USA...) and innovate to supply other protein sources to their market (fermentation, insects). This research contributes to the literature by offering practical insights into the marketing strategies needed to boost AP-adoption in France. In the literature review, we cover the diversity of APs, and the positioning, promotion and distribution issues involved in bringing this type of product to market effectively. Through interviews with players in the food sector, as well as a survey of a French panel, we provide a better understanding of the relationship and expectations of the various stakeholders involved. The results highlight the need to broaden the consumer target beyond vegetarians, leveraging flexitarian and omnivorous individuals. Key recommendations include the organization of tastings to overcome consumer skepticism, innovative packaging and labeling, and enhanced communication. Distribution strategies should focus on integrating products across multiple retail formats and offering alternative products on out-of-home catering and e-commerce channels. Addressing price competitiveness through commercial offers and loyalty programs is also a crucial lever to drive trial and adoption. Moreover, fostering transparency and educating consumers about product benefits are essential to build trust. Managerial implications include recommendations for collaboration between producers, retailers, and public stakeholders. The main limitation of this study is the emerging nature of the market that makes it challenging to observe long-term trends. Future research could build on these findings by conducting similar studies tracking the impact of marketing strategies over time and expanding the analysis to other countries.